O processo da tomada de decisão em estupradores de vulneráveis em ambientes intra e extrafamiliar - Costa, Christian da Silva (2023)
The aim of this research is to understand the decision-making process in vulnerable rapists who commit abuse in an intra and extra-family environment. The research was carried out with 80 adult males between 18 and 75 years who had been duly tried and convicted under Article 217A (rape of vulnerable) and serving time in a penitentiary in the State of São Paulo. All individuals within this criterion were submitted to a forensic clinical interview and evaluated by the tests (FDT, PFISTER and HTP). In the application of the HTP test, they were also asked to draw a child, in addition to the traditional human figure. Of the total group of 80 individuals, 61 were from the intrafamilial group and 19 from the extrafamilial group. It was observed in this study that intra and extrafamily abusers have an insignificant percentage of cognitive distortion with regard to the interpretation of the child's desire. Results also showed that the significant majority of the individuals evaluated here do not have significant impairment of inhibition or inhibitory control, thus having greater preservation and control of their will, if they so wish. Impulsivity is indeed present in these individuals. However, this impulsiveness found here is acting out, that is, through impulsive actions, these individuals seek to relieve mental tensions. The decision process that leads to the act of abuse is not associated with a disease or mental disorder, but with a human behavioral repertoire. From the data of this study, we understand that categorized mental disorders are not the only, nor the best way to explain this criminal behavioral phenomenon